+0  
 
0
30
1
avatar

simplify 

(8𝑥6𝑦4)(5𝑥5𝑦12)

 Mar 24, 2021
 #1
avatar+721 
+2

I'll assume you mean \((8x^6y^5)(5x^5y^{12})\). this can be expressed as \(8 \cdot 5 \cdot x^6 \cdot x^5 \cdot y^4 \cdot y^{12}\)

 

\(8\) times \(5\) is \(40\)

using a law of exponents which states that \(a^n \cdot a^m = a^{n + m}\), we can write \(x^6 \cdot x^5 = x^{11}\) and \(y^4 \cdot y^{12} = y^{16}\).

 

so, we have \(40 \cdot x^{11} \cdot y^{16} = 40x^{11}y^{16}\) 

 

and there you have it

 Mar 24, 2021

17 Online Users

avatar